2004
DOI: 10.1002/ajmg.b.30047
|View full text |Cite
|
Sign up to set email alerts
|

Variants of the orexin2/hcrt2 receptor gene identified in patients with excessive daytime sleepiness and patients with Tourette's syndrome comorbidity

Abstract: The orexin-2/hypocretin-2 (OX2R) receptor gene is mutated in canine narcolepsy and disruption of the prepro-orexin/hypocretin ligand gene results in both an animal model of narcolepsy and sporadic cases of the human disease. This evidence suggests that the structure of the OX2R gene, and its homologue, the OX1R gene, both members of the G protein-coupled receptor (GPCR) family, and the gene encoding the peptide ligands, the prepro-orexin/hypocretin gene, may be variables in the etiology of sleep disorders. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 79 publications
1
35
0
Order By: Relevance
“…In humans, another idiopathic sleep disorder termed excessive daytime sleepiness has been linked by single-stranded conformational polymorphism analysis to an HCRTr2 coding variant resulting in a Pro11Thr change that impaired HCRT ligand binding-related signaling 13 . These findings suggest that alterations in HCRT ligand or its receptors can disrupt neurotransmission and may play key roles in sleep-related disorders, including narcolepsy.…”
Section: Narcolepsymentioning
confidence: 99%
“…In humans, another idiopathic sleep disorder termed excessive daytime sleepiness has been linked by single-stranded conformational polymorphism analysis to an HCRTr2 coding variant resulting in a Pro11Thr change that impaired HCRT ligand binding-related signaling 13 . These findings suggest that alterations in HCRT ligand or its receptors can disrupt neurotransmission and may play key roles in sleep-related disorders, including narcolepsy.…”
Section: Narcolepsymentioning
confidence: 99%
“…Some authors found a variant of orexin genes, which have been shown to be essential for normal sleep in patients with TS+ADHD. 54 correlated with the number of comorbidities. In addition to that, psychosocial factors are also very important, as an external locus of control (LOC) is associated with an increased risk of anxiety disorders.…”
Section: Sleep Disordersmentioning
confidence: 99%
“…Samples were denatured at 951C for 5 min and chilled to 41C for 5 min before loading. The entire volume of buffer and PCR product, 18 ml, was loaded into separate wells of Novex 4-20% tris-boric acid-EDTA (TBE) gels [40,41] and run at 151C using 80 V for 19 h to resolve the PCR fragments. The DNA was visualized using the Novex SilverXpress Staining Kit (Uppsala, Sweden).…”
Section: Sequence Variant Detection In the Cyslt 1 Receptor Genementioning
confidence: 99%
“…LTD 4 -induced calcium mobilization in cells expressing G300S variants and I206S variants was compared with CysLT 1 wild-type. Maximum fluorescence levels were measured in a Molecular Devices Fluorometric Imaging Plate Reader [47] as reported previously [26,41].…”
Section: Culture and Transfection Of Cellsmentioning
confidence: 99%